2017
DOI: 10.5455/jtomc.2017.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Assesment of the effect of summer camp on the life quality of diabetic children

Abstract: Aim: Type 1 diabetes which is a chronic metabolic disease can affect the quality of life of a person. The aim of this study is to evaluate the life quality of diabetic children and adolescents who are diagnosed with type 1 diabetes mellitus and compare the perceptions of life quality through the life quality scale before and after summer camp. Materials and Method: A scale of life quality was applied to 31 children/adolescents with type 1 Diabetes Mellitus between ages 9-16 years in the Diabetes Summer Camp. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
1
Order By: Relevance
“…Furthermore, no effect was observed on young people’s dimensions of HRQoL. This finding contradicts previous findings which showed that participation in such programs led to a significant improvement in children and adolescents’ self-esteem [ 34 , 35 ]. These findings may be attributed to the QoL dimensions measured.…”
Section: Discussioncontrasting
confidence: 85%
“…Furthermore, no effect was observed on young people’s dimensions of HRQoL. This finding contradicts previous findings which showed that participation in such programs led to a significant improvement in children and adolescents’ self-esteem [ 34 , 35 ]. These findings may be attributed to the QoL dimensions measured.…”
Section: Discussioncontrasting
confidence: 85%